Oxidized Carbon-Based Spacers for Pressure-Resistant Graphene Oxide Membranes - Ekaterina A. Chernova; Konstantin E. Gurianov; Dmitrii I. Petukhov; Andrei P. Chumakov; Rishat G. Valeev; Victor A. Brotsman; Alexey V. Garshev; Andrei A. Eliseev (Membranes, 2022)
In this study, we report the influence of carbon-based spacer-oxidized derivatives of fullerenes (fullerenols) C60(OH)26–32 and graphene oxide nanoribbons on the performance and pressure stability of graphene-oxide-based composite membranes. The impact of the intercalant shape and composition on the permeance of the selective layers for water vapors has been studied under pressure gradients. It is shown that the insertion of ball-shaped fullerenols between graphene oxide nanoflakes allows a suppression in irreversible permeance loss to 2–4.5% and reversible permeance loss to <25% (at 0.1 MPa), while retaining large H2O/N2 selectivities of up to ~30,000. The demonstrated approach opens avenues for the highly effective stabilization of GO membranes at elevated pressures for industrial-scale dehumidification.